Factors Related to Work Fatigue in Oil Palm Farmers - Pohan, Arja Adi Jaya; Arrazy, Syafran; Utami, Tri Niswati (Indonesian Journal of Global Health Research, 2024)
Every year 2 million workers die due to work accidents caused by fatigue. This research aims to determine the factors related to work fatigue in oil palm farmer workers in Tanjung Medan Labuhanbatu Village. The research method used is descriptive quantitative with a cross-sectional research design. The population of workers is 104 people and the sample is 85 people. The sampling technique uses simple random sampling. The results of the analysis showed that there was a relationship between age and work fatigue (p-value = 0.000) r = 0.607, there was a relationship between length of service and work fatigue (p-value 0.000) r = 0.526, there was a relationship between length of work and work fatigue (p-value 0.010) r = 0.078, there is a relationship between workload and work fatigue (p-value 0.012) r = 0.647, there is no relationship between nutritional status and work fatigue (p-value 0.353) r = 0.049. This research concludes that there is a relationship between age, length of service, length of work, and workload on work fatigue, there is no relationship between nutritional status and work fatigue in oil palm farmers. Advice for workers is that they should pay attention to their health while working to avoid work fatigue which could pose a risk of work accidents.